Early–middle Permian Mediterranean gorgonopsian suggests an equatorial origin of therapsids - Rafel Matamales-Andreu; Christian F. Kammerer; Kenneth D. Angielczyk; Tiago R. Simões; Eudald Mujal; Àngel Galobart; Josep Fortuny (Nature Communications)
Abstract Therapsids were a dominant component of middle–late Permian terrestrial ecosystems worldwide, eventually giving rise to mammals during the early Mesozoic. However, little is currently known about the time and place of origin of Therapsida. Here we describe a definitive therapsid from the lower–?middle Permian palaeotropics, a partial skeleton of a gorgonopsian from the island of Mallorca, western Mediterranean. This specimen represents, to our knowledge, the oldest gorgonopsian record worldwide, and possibly the oldest known therapsid. Using emerging relaxed clock models, we provide a quantitative timeline for the origin and early diversification of therapsids, indicating a long ghost lineage leading to the evolutionary radiation of all major therapsid clades within less than 10 Myr, in the aftermath of Olson’s Extinction. Our findings place this unambiguous early therapsid in an ancient summer wet biome of equatorial Pangaea, thus suggesting that the group originated in tropical rather than temperate regions.